A case of severe osteomalacia caused by Tubulointerstitial nephritis with Fanconi syndrome in asymptomotic primary biliary cirrhosis. Issue 1 (December 2015) - Yamaguchi, Shintaro; Maruyama, Tatsuya; Wakino, Shu; Tokuyama, Hirobumi; Hashiguchi, Akinori; Tada, Shinichiro; Homma, Koichiro; Monkawa, Toshiaki; Thomas, James; Miyashita, Kazutoshi; Kurihara, Isao; Yoshida, Tadashi; et al.
Abstract Background Primary biliary cirrhosis (PBC) is an immune-mediated chronic cholestatic liver disease, characterized by increased concentrations of serum IgM and the presence of circulating anti-mitochondrial antibodies. Although bone diseases such as osteoporosis or osteodystrophy are commonly associated with PBC, osteomalacia which is caused by abnormal vitamin D metabolism, mineralization defects, and phosphate deficiency has not been recognized as a complication of PBC. Case presentation We report the case of a 49-year-old Japanese woman who complained of multiple fractures. Hypophosphatemic osteomalacia was diagnosed from a low serum phosphorus level, 1, 25-dihydroxyvitamin D3 level, high levels of bone specific alkaline phosphatase and the findings of bone scintigraphy, although a bone biopsy was not performed. Twenty four hour urine demonstrated a low renal fractional tubular reabsorption of phosphate, increased fractional excretion of uric acid and generalized aminoaciduria. An intravenous bicarbonate loading test suggested the presence of proximal renal tubular acidosis (RTA). These biochemical data indicated Fanconi syndrome with proximal RTA. A kidney biopsy demonstrated the features of tubulointerstitial nephritis (TIN). The patient was also suspected as having primary biliary cirrhosis (PBC) because of high levels of alkaline phosphatase, IgM and the presence of anti-mitochondrial M2 antibody, though biochemical liver function was normal. Sequential liver biopsy was compatible with PBC and the diagnosis of PBC was definite. After administration of 1, 25 dihydroxyvitamin D3, neutral potassium phosphate, sodium bicarbonate for osteomalacia and subsequent predonizolone for TIN, symptoms of fractures were relieved and renal function including Fanconi syndrome was ameliorated. Conclusion In this case, asymptomatic PBC was shown to induce TIN with Fanconi syndrome with dysregulation of electrolytes and vitamin D metabolism, which in turn led to osteomalacia with multiple fractures. Osteomalacia has not been recognized as a result of the renal involvement of PBC. PBC and its rare complication of TIN with Fanconi syndrome should be considered in adult patients with unexplained osteomalacia even in the absence of liver dysfunction.